2021
DOI: 10.1007/s11356-021-13498-1
|View full text |Cite
|
Sign up to set email alerts
|

Can CO2 emissions and energy consumption determine the economic performance of South Korea? A time series analysis

Abstract: Following the United Nations Sustainable Development Goals (UN-SDGs), which place emphasis on relevant concerns that encompass access to energy (SDG-7) and sustainable development (SDG-8), this research intends to reexamine the relationship between urbanization, CO 2 emissions, gross capital formation, energy use, and economic growth in South Korea, which has not yet been assessed using recent econometric techniques, based on data covering the period between 1965 and 2019. The present study utilized the autore… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 132 publications
(70 citation statements)
references
References 72 publications
20
50
0
Order By: Relevance
“…In line with the studies of Awosusi et al [3], Alola et al [37] and Sarkodie et al [38], we added GDP into the model. Furthermore, following the studies of Adebayo et al [21], Rjoub et al [39] and He et al [24], we incorporate energy use into the model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with the studies of Awosusi et al [3], Alola et al [37] and Sarkodie et al [38], we added GDP into the model. Furthermore, following the studies of Adebayo et al [21], Rjoub et al [39] and He et al [24], we incorporate energy use into the model.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of air contamination and severe weather conditions, as is regularly witnessed, pose substantial health risks to humans [2]. In this respect, it is critical to pay significant awareness to the topic of climate change; else, the dangers and concerns associated with climate change, which are predicted to rise in the future years, will have disastrous consequences for safety and human health [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In line with the studies of [13,30,40], we added GDP into the model. Moreover, following the studies of [17,29], we incorporated the URB into the model. Lastly, we introduced HYDRO into the model following the studies of [11,30,41,42].…”
Section: Empirical Methodologymentioning
confidence: 99%
“…Their empirical outcomes revealed that both urbanization and GDP caused degradation of the environment, while financial development mitigated CO 2 . The study of Awosusi et al [29] in South Korea on the association between CO 2 and globalization, utilization of energy, and energy use using data from 1965 to 2019 showed that globalization and GDP triggers CO 2 . In China, Soylu et al [13] assessed the CO 2 -GDP-REC association using the novel wavelet coherence and causality approaches.…”
Section: Empirical Reviewmentioning
confidence: 99%
See 1 more Smart Citation